Effect of gamma-ray irradiation on isothermal crystallization of biodegradable poly(ethylene succinate). Issue 25 (1st September 2016) - Chuang, Yu-Fan; Chou, Yu-Cheng; Yang, Fuqian; Lee, Sanboh
Abstract: The effects of gamma-ray irradiation on the isothermal crystallization of biodegradable poly(ethylene succinate) (PESu) and the growth behavior of PESu spherulites have been studied by differential scanning calorimetry and polarized optical microscopy. The irradiation doses used in the study are 0, 200, 400, and 600 kGy. The kinetic parameters for the isothermal crystallization have been determined, using the Avrami relationship. The nucleation constants and activation energy for the growth of the PESu spherulites have been analyzed, using the Lauritzen-Hoffman growth theory. Triple melting points have been observed for all the irradiated PESu. The gamma irradiation has no observable effect on the Avrami exponent, and the composite rate constant increases first with the increase of the crystallization temperature, reaches maximum at the crystallization temperature of ~35 °C, and then decreases with the increase of the crystallization temperature for both the non-irradiated and irradiated PESu. There exists a transition of the growth of the PESu spherulites from regime II to regime III. Both the nucleation constants and activation energy increase with increasing the irradiation dose. The gamma irradiation increases the energy barrier for the migration of polymer chains.